2022
DOI: 10.1097/qai.0000000000002918
|View full text |Cite
|
Sign up to set email alerts
|

Disengagement From HIV Care and Failure of Second-Line Therapy in Nigeria: A Retrospective Cohort Study, 2005–2017

Abstract: Background: Understanding the correlates of disengagement from HIV care and treatment failure during second-line antiretroviral therapy (ART) could inform interventions to improve clinical outcomes among people living with HIV (PLHIV). Methods:We conducted a retrospective cohort study of PLHIV aged .15 years who started second-line ART at a tertiary center in Nigeria between 2005 and 2017. Participants were considered to have disengaged from care if they had not returned within a year after each clinic visit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A meta-analysis study found that the overall prevalence of syphilis among HIV-infected patients in China reached 19.9% ( 29 ), 7.3% in sub-Saharan Africa ( 34 ) and 19.9% in France ( 35 ). The 5.6% syphilis infection in our study was lower than the above results, the rationale for this was: our study participants were PLWH with viral suppression, who themselves had higher adherence and lower risk behaviors ( 36 ). Syphilis has emerged as a major public health threat, particularly among MSM in China who have a high incidence of syphilis and HIV/syphilis co-infection ( 33 ).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A meta-analysis study found that the overall prevalence of syphilis among HIV-infected patients in China reached 19.9% ( 29 ), 7.3% in sub-Saharan Africa ( 34 ) and 19.9% in France ( 35 ). The 5.6% syphilis infection in our study was lower than the above results, the rationale for this was: our study participants were PLWH with viral suppression, who themselves had higher adherence and lower risk behaviors ( 36 ). Syphilis has emerged as a major public health threat, particularly among MSM in China who have a high incidence of syphilis and HIV/syphilis co-infection ( 33 ).…”
Section: Discussionmentioning
confidence: 47%
“…The possible reasons were: first the participants in this study are HIV-infected patients who had HIV virally suppressed and had good treatment compliance. People with low levels of education tend to have poor adherence to treatment, resulting in unsuppressed HIV viral load ( 36 ). Therefore, they were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Disengagement from care is also a significant problem, although it is possible to re-engage with a substantial proportion of cases, 55 highlighting the benefits that can be gained through outreach and tracing efforts. Given that INSTI-based long-acting injectables are being considered as pre-exposure prophylaxis, 56 it is crucial to conduct further analyses of resistance across SSA over extended periods and to monitor newly diagnosed individuals for INSTI resistance.…”
Section: Discussionmentioning
confidence: 99%